2014
DOI: 10.1037/tam0000023
|View full text |Cite
|
Sign up to set email alerts
|

Stalking and age.

Abstract: Few data exist concerning older and younger stalkers. This study compares 3 age groups of stalker [aged 16 or under (n = 19), aged 17–59 (n = 1,499), aged 60 or over (n = 86)] on 83 variables pertaining to demographics, the stalking process, the impact of stalking, and victim and third party responses. Self-defined victims of stalking provided the data. Just 11 of the variables differed significantly by age group. All 3 age groups were equally violent. Older victims of stalking were doubly disadvantaged, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The age–crime curve posits that adolescents and young adults are more likely than other age groups to engage in offending and delinquent behavior (Farrington et al, 2008). Previous work has suggested that the age of onset may be higher for stalkers than for other types of crime (Nobles et al, 2009) and that older stalkers can be as dangerous as younger stalkers (Sheridan et al, 2014). This may explain why age was not significant in our first three stalking recidivism models but was significant in our general recidivism model.…”
Section: Discussionmentioning
confidence: 99%
“…The age–crime curve posits that adolescents and young adults are more likely than other age groups to engage in offending and delinquent behavior (Farrington et al, 2008). Previous work has suggested that the age of onset may be higher for stalkers than for other types of crime (Nobles et al, 2009) and that older stalkers can be as dangerous as younger stalkers (Sheridan et al, 2014). This may explain why age was not significant in our first three stalking recidivism models but was significant in our general recidivism model.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of stalking victimization have examined stalking as it relates to various factors that include sex (e.g., Sheridan, North, & Scott, 2014), age (e.g., Sheridan, Scott, & North, 2014), culture (e.g., Chapman & Spitzberg, 2003), prior relationship status (e.g., Sheridan & Lyndon, 2012), and lifestyle factors (e.g., Reyns, Henson, Fisher, Fox, & Nobles, 2015). However, research to date has not examined a potentially at-risk group, namely, individuals identifying as lesbian, gay, bisexual, transgender, intersex, or queer (LGBTIQ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we were unable to compare the ages of stalkers and victims because of insufficient data on the ages of stalkers. However, findings from a prior study by Sheridan et al (2014) shed light on age-related stalking patterns. Younger stalkers were inclined to target individuals within their age group or their parents’ age group.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, older stalkers, especially those aged older than 60, showed a tendency to target younger individuals. In general, older victims were found to be in greater need of support, facing a higher risk of experiencing physical harm as they are more likely to be injured (McGarry et al, 2011; Sheridan et al, 2014). Given that our findings indicate a higher number of older victims of Aggressors, it is probable that they are the ones most in need of support to mitigate the risk of physical harm.…”
Section: Resultsmentioning
confidence: 99%